2015
DOI: 10.15448/1980-6523.2015.3.12849
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da higiene bucal de crianças com deficiência mental

Abstract: Objective: To identify factors associated with the quality of oral hygiene in children with mental disabilities. Methods: A cross-sectional study was conducted with a sample of 181 mentally disabled children aged three to 12 years and their mothers. The study was conducted in two public hospitals of medical care for special children in the city of Rio de Janeiro, southeastern Brazil. The children were examined on the quality of oral hygiene and presence of caries lesions. The examiner was previously calibrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The Simplified Oral Hygiene Index (OHI-S) was used to evaluate oral hygiene and was scored as follows: 0 = Absence of dental plaque/dental calculus; 1 = little dental plaque/dental calculus, less than 1/3 of dental surface covered; 2 = dental plaque / dental calculus covering more than 1/3 and less than 2/3 of the dental surface; and 3 = dental plaque/dental calculus covering more than 2/3 of dental surface. Plaque and dental calculus were evaluated separately [17, 21, 30]. The final result of the OHI-S was obtained from the sum of the codes divided by the total number of teeth examined and classified as satisfactory (0 to 1), fair (1.1 to 2), deficient (2.1 to 3) or poor (≥3.1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Simplified Oral Hygiene Index (OHI-S) was used to evaluate oral hygiene and was scored as follows: 0 = Absence of dental plaque/dental calculus; 1 = little dental plaque/dental calculus, less than 1/3 of dental surface covered; 2 = dental plaque / dental calculus covering more than 1/3 and less than 2/3 of the dental surface; and 3 = dental plaque/dental calculus covering more than 2/3 of dental surface. Plaque and dental calculus were evaluated separately [17, 21, 30]. The final result of the OHI-S was obtained from the sum of the codes divided by the total number of teeth examined and classified as satisfactory (0 to 1), fair (1.1 to 2), deficient (2.1 to 3) or poor (≥3.1).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies have suggested that access to dental services is more difficult for individuals with special needs [9, 10, 1720]. The difficulty in adequately performing oral hygiene due to the limitations imposed by disease and a lack of information on the part of parents or caregivers about the importance of oral health care can place individuals with special needs in a vulnerable position with regard to dental caries [10, 12, 13, 15, 1821].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Cognitive impairment can also exert a negative impact on OHRQoL by limiting one's independence with regards to oral hygiene, which, when neglected, can lead to consequences such as periodontal disease and dental caries. 11,13,14,15,16,17,23 In the present study, only malocclusion exerted a significant negative impact on the OHRQoL of the individuals with MPS, as evidenced by the total P-CPQ score and scores on the oral symptoms, functional limitations and wellbeing domains. Malocclusion may be due to the skeletal and joint abnormalities these individuals have due to the deposition of GAGs in the head and neck region.…”
Section: Discussionmentioning
confidence: 45%
“…Each surface receives a code ranging from zero to three based on the amount of calculus and bacterial plaque. 22,23 Malocclusion was recorded based on Oliveira et al 24 and the WHO criteria: 21 horizontal overjet (increased/ diminished, negative/anterior crossbite), vertical overjet/overbite (increased/deep bite, diminished, negative, top-to-top) and posterior crossbite. When at least one condition was diagnosed, the subject was classified as having an occlusal problem resulting from an abnormal vertical or transverse occlusion.…”
Section: Clinical Data Collectionmentioning
confidence: 99%